English Language Teachers' Perceptions and Practices on Learner Autonomy in Nepalese Context - Bhattarai, Prakash (REiLA : Journal of Research and Innovation in Language, 2021)
Learner autonomy is the ability and responsibility of learners to take control of their learning. Motivation, the chance to work independently and/ or collaboratively, access to the internet and library, and challenging tasks promote learner autonomy. This study explores English language teachers' perceptions and practices on learner autonomy and finds the difference in the perceptions and practices by their sex, level, qualification, and type of school they teach. One hundred thirty-three (133) teachers teaching at Tulsipur Sub-metropolitan Dang, Nepal, were selected using the fishbowl technique. Data drawn with the questionnaire's help were analysed via univariate (frequency, percentage, and median) and bivariate (t-test and Cohen's d) analysis. From the analyses, it was found that English language teachers teaching at different levels are aware of the what, why, and how of learner autonomy, and they promote learner autonomy by engaging and encouraging students to be involved in the tasks which promote learner autonomy. Perceptions on learner autonomy do not differ by their sex, level, qualification, and type of school they teach. Likewise, practices on learner autonomy also do not differ by the sex and level of the teachers, but their practices differ by the type of school where they teach and their qualification.